Dualisme Pemerintahan Desa Dinas dan Desa Pakraman di Kelurahan Peguyangan - I Komang Arya Triadi; Anak Agung Bagus Bayu Anggawirya; Kadek Putra Santika Narayana Narayana; Made Arya Adiartha; Tjokorda Gede Dalem Suparsa (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2023)
The village governance system in Bali is divided into two forms, namely Desa Dinas and Desa Pakraman. Desa Pakraman, as a traditional village with its leadership, has a strong influence on its residents, while Desa Dinas is limited to administrative matters. This causes an overlap in the leadership and authority of both Desa Dinas and Desa Pakraman. Peguyangan Sub-district is one that adopts this governance system, with two systems from Peguyangan Sub-district and Peguyangan Traditional Village. The governing subjects of Desa Dinas and Desa Pakraman are the same, which is the community of Peguyangan Sub-district, leading to an overlapping of governance in Peguyangan Sub-district. This research employs a qualitative method. The overlapping of Desa Dinas and Desa Pakraman governance is manifested in 1) the existence of the PKK overlapping with Banjar Istri, and 2) the use of traditional banjar apparatus for Desa Dinas activities.